Influence of extracellular K+ or Mg2+ on the stages of the antifungal effects of amphotericin B and filipin. - Brajtburg, J (1980)
The macrolide heptaene amphotericin B (AmB) induced concentration-dependent effects on Saccharomyces cerevisiae which were separable into two distinct stages. At low concentrations the drug inhibited the growth of the yeast and reversible changed cell permeability to Na+ and K+. At high levels it was lethal. The intracellular K+ concentration of cells with reversible damage (stage I) could be increased by addition of K+ to the medium, but cells irreversibly damaged (stage II) were not able to retain K+. The addition of K+ to the medium did not influence the growth-inhibitory or killing action of AmB. Addition of Mg2+ to cultures increased S. cerevisiae resistance to the killing effects of AmB. At low concentrations of AmB, growth inhibition was also decreased by extracellular Mg2+, but at higher concentration of AmB, growth inhibition was increased, probably because the prevention by Mg2+ of the lethal effect allowed expression of the inhibitory effect in a greater range. Simultaneous addition of K+ and Mg2+ markedly decreased both the inhibitory and lethal action of AmB at all concentrations. Filipin, a pentaene macrolide, had only lethal effects, which were unaffected when K+ was added to the medium but were diminished when medium was supplemented with Mg2+.